Total Quality Management, Budaya Organisasi Dan Motivasi Kerja Terhadap Kinerja Karyawan - Mukhtar Tahir (STIE Amkop Makassar, 2022)
Employee performance has a very important meaning in a company to achieve big profits because it can make a big contribution to company profits. This study aims to determine the effect of Total Quality Management (TQM), Organizational Culture and work motivation on the performance of employees of PT Bosowa Propertindo Makassar. The approach used in this study is a quantitative approach to test hypotheses with a relationship between variables or a causal relationship. The population in this study were all employees of PT Bosowa Propertindo Makassar, totaling 35 people. The sampling of this research was carried out using a saturated sampling technique (census), so that the sample used in this study were all 35 employees of PT Bosowa Propertindo Makassar. The data were collected by research in the form of scores on the questionnaire. Then, the analytical technique used is multiple linear regression analysis. The results of the study found that total quality management, organizational culture and work motivation both simultaneously and partially had a positive and significant effect on employee performance at PT Bosowa Propertindo Makassar.